BEHAVIORAL DETERMINANTS WORKERS IN THE USE OF PPE BASED ON HAZARD ASSESSMENT IN FOUNDRY COMPANY CEPER KLATEN - Ireng Sigit Atmanto (Prosiding SNST Fakultas Teknik, 2011)
Foundry industry is an industry body to process ore into finished metal. In Klaten Ceper foundry in this work with the iron foundry casting temperature reaches 1600 ° C. In this industry most workers are not using personal protective equipment in the working environment although there are threats of environmental hazards such as high temperature, infrared radiation, hot metal splash, dust from burning, electric induction, and bits of metal materials. This study is an exploratory qualitative research with respondents eight people consisting of seven people working at the foundry and one person working on finishing division. Collecting data through direct observation by checklist and in-depth interviews using questionnaires. The results of this study indicate that the practice of the use of PPE at foundry industry can not be implemented. Based on in-depth interviews obtained information that factors into the determinants of workers not using PPE is the physical work environment factors and management who have not applied the system of occupational safety and health. Advised the company to prepare regulations, require the use of PPE and provide opportunities for workers to follow safety and health training, and creating a comfortable working environment. PPE need to be designed for metal foundry in the tropics thus providing convenience for its users but still meet the standards of occupational safety and health. Keywords: Behavior, PPE, Hazard Assessment, Metal Casting